2016
DOI: 10.1103/physrevb.93.125428
|View full text |Cite
|
Sign up to set email alerts
|

Direct band gaps in group IV-VI monolayer materials: Binary counterparts of phosphorene

Abstract: We perform systematic investigation on the geometric, energetic and electronic properties of group IV-VI binary monolayers (XY), which are the counterparts of phosphorene, by employing density functional theory based electronic structure calculations. For this purpose, we choose the binary systems XY consisting of equal numbers of group IV (X = C, Si, Ge, Sn) and group VI elements (Y = O, S, Se, Te) in three geometrical configurations, the puckered, buckled and planar structures. The results of binding energy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
135
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(164 citation statements)
references
References 59 publications
27
135
0
2
Order By: Relevance
“…It clearly demonstrates that oxides exhibit a distinct character from those of sulphides, selenides, and tellurides. Recently, a similar trend has also been observed in both group IV-VI [19] and group II-VI monolayers [51].…”
Section: A Atomic Structure and Energeticssupporting
confidence: 79%
See 2 more Smart Citations
“…It clearly demonstrates that oxides exhibit a distinct character from those of sulphides, selenides, and tellurides. Recently, a similar trend has also been observed in both group IV-VI [19] and group II-VI monolayers [51].…”
Section: A Atomic Structure and Energeticssupporting
confidence: 79%
“…These investigations resulted in the discovery of many 2D families such as group IV and group III-V binary compounds in honeycomb structure [17]. Very recently, theoretical studies have reported a stable class of single-layer group IV monochalcogenides (Y X, Y = Si, Ge, Sn and X = S, Se, and Te) that are semiconductors with * seymur@unam.bilkent.edu.tr wide band gaps [18][19][20]. Furthermore, a study focused on the structural and electronic properties of these systems reported indirect-direct band gap transitions under small mechanical strain [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a two‐dimensional (2D) material with an analogous structure as black phosphorus, yet with a finite band gap unlike graphene, tin sulfides have gained considerable attention among the family of two‐dimensional (2D) materials . Among tin sulfides, SnS (tin monosulfide, Herzenbergite) is known as a potential candidate for solar energy utilization due to its fascinating electronic properties such as direct optical band gap (1.4–1.7 eV) and a high absorption coefficient (>10 4 cm −1 ), in addition to the fact that it is earth‐abundant, non‐toxic and air stable .…”
Section: Introductionmentioning
confidence: 99%
“…This 2D nature of the SnS layer renders only a weak interaction between neighboring layers via van der Waals interactions, which allows easy separation and fabrication of layered composite structures with highly disparate atomic layers to create a wide range of van der Waals (vdWs) heterostructures without any constraints of lattice match and compatibility. Therefore, the processability of SnS combined with its extraordinary physical and chemical properties makes it a perfect model system in exploring new 2D properties …”
Section: Introductionmentioning
confidence: 99%